Co-design of Guidance for Patient and Public Involvement in Psychedelic Research - Close, James B.; Bornemann, Julia; Piggin, Maria; Jayacodi, Sandra; Luan, Lisa Xiaolu; Carhart-Harris, Robin; Spriggs, Meg Jo (Frontiers in Psychiatry, 2021)
Within the context of scientific research, patient and public involvement (PPI) is defined as research performed ‘with’ or ‘by’ patients and members of the public, rather than ‘to’, ‘about’ or ‘for’ them. When carried out systematically and thoughtfully, PPI has the potential to strengthen the quality and impact of research by fostering accountability, transparency, and relevance. There exist numerous guidelines, frameworks and tools for supporting PPI, however, these do not account for the unique challenges faced in psychedelic research. This paper describes the co-design of guidance intended to help build, evaluate and improve PPI in psychedelic research. A steering group was formed to design and run a co-design workshop alongside public collaborators. Insights from this workshop were analysed and refined into a comprehensive and readily usable guide for planning PPI specific to the field of psychedelic research. Core values emerging from the process focused on the essential importance of trust, learning, purpose and inclusivity. It is hoped that this guidance will be a starting point for incorporating PPI in future psychedelic research, so that it can grow and adapt as this burgeoning field of research progresses.